Penjahat Dunia Maya: Studi Litratur Permasalahan Etika Pada Teknologi Informasi - adi wijaya wijaya (Institute of Information Technology and Social Science (IITSS), 2021)
This research is intended to delve into the ethical issues associated with the growth of information technology and its security, particularly within the scope of the internet or cyberspace. The study utilizes information from various journals to discuss issues related to cybercrimes such as hacking, legal violations, and cybersecurity itself. The analysis is conducted in depth so that we can all understand and formulate actions related to these cybercrimes.